Development of the hybrid storage system using thermoelectric generator - Ong, Wei Chao (2022)
Thermoelectric module (TEM) is a solid-state semiconductor with n-type and p-type materials interconnected by metal strips. The module is only a small thin flat plate with no moving parts, but it can convert the electrical energy into thermal energy and vice versa. It can be used as a heat pump under Peltier effect or an electric generator under Seebeck effect. In this study, the thermoelectric module will be used as a heat pump, where it requires current input to create a cold side and a hot side on its surface to transfer the heat from one side to the other. There is no available hybrid storage system in the market that supports both heating and cooling effects. Therefore, this study will provide an insight on the application of simultaneous cooling and heating chambers by TEM. A CFD simulation model is performed by using ANSYS software to investigate the performance of TEM under heat load condition. Then, two insulation chambers are built to analyze the performance of TEM when it is used for cooling or heating purpose. Three operation modes are studied in this paper, which are cooling mode, heating mode and simultaneous cooling and heating mode. Under cooling mode, the air temperature inside the chamber able to reach 5.89 °C within 30 minutes, meanwhile the chamber reaches 61.66 °C within 25 minutes under heating mode. On the other side, the cooling chamber reaches 9.66 °C and the heating chamber reaches 39.09 °C for the simultaneous mode, the two chambers achieve equilibrium state within 20 minutes of operation. The experimental COP of the chamber for cooling mode is 0.05 while the heating mode is 0.12